Intimal Surface Suture Line (End-Product) Assessment of End-to-Side Microvascular Anastomosis. Issue 7 (July 2017) - Pafitanis, Georgios; Veljanoski, Damjan; Ghanem, Ali M.; Myers, Simon
Abstract : Summary: Microsurgery simulation courses increasingly use assessment methodologies to evaluate the quality of microvascular anastomosis and to provide constructive feedback in competency-based training. Assessment tools evaluating the "journey" of skill acquisition in anastomosis have evolved, including global rating scores, hand motion analysis, and evaluation of the final outcome, that is, "end-product" assessment. Anastomotic patency is the gold standard end-product in clinical microvascular surgery, and in vivo end-to-side anastomosis, which can be confirmed using the Acland-test. Microsurgery simulation training is moving to include nonliving models, where possible, according to the principles of the replacement, reduction, and refinement of the use of animals in research. While a standardized end-product assessment tool for nonliving end-to-end anastomosis exists, there is no similar tool for end-to-side anastomosis. Intimal surface suture line assessment is an error list-based tool, which involves exposing the intimal surface of a vessel and analysis of the quality of suture placement. Errors in end-to side anastomosis were classified according to the potential clinical significance (high, medium, or low) perceived by the senior authors. Intimal surface suture line assessment provides constructive feedback during microsurgery training, helping to minimize technical errors, which are likely to impact on the final outcome in a clinical environment. Intimal surface suture line assessment lends itself to nonliving simulation training courses as an end-product self-assessment tool, especially during the early learning curve, to demonstrate progression. It has intraoperative relevance by assessment of the intimal surface suture line as the final sutures are placed in an end-to-side anastomosis to provide objective feedback to trainees in relation to likely physiological anastomotic outcome.